FORMULATION AND EVALUATION OF GEL MASK PEEL OF BLACK GLUTINOUS RICE EXTRACT (ORYZA SATIVA VAR GLUTINOSA) AND GREEN TEA (CAMELIA SINENSIS) (Jurnal Mitra Kesehatan, 2021)
Introduction: Black glutinous rice (Oriza sativa var glutinosa) and green tea (Camelia sinensis) are plants that are useful for moisturizing the skin. The purpose of this study was to obtain the best formulation of peel-off gel mask preparations from black glutinous rice and green tea extract. Method: The gel mask formulation was made on the basis of variations in the concentration of Hydroxy Propyl Methyl Cellulose (HPMC) of F1 (2,5%), F2 (3%) and F3 (3,5%) with evaluation including organoleptic tests, pH, viscosity, homogenity, dispersity test, and drying time at temperatures of 4oC, 25oC, 40oC for 28 days. Results: The evaluation results of the three formulations met the requirements for a good peel-off gel mask. pH results are between 4.6-5.5 which is still in the standard range of 4.5-6.0. The results of the viscosity test are 6.500-12.166.7 cps which are in the range of 6.000-24.000 cps, the dispersion area meets the requirements of 5-7 cm, the result of the drying time is 15-22 minutes which are in the range of 15-30 minutes. Conclusion: The conclusion of this study was that F1, F2, and F3 met all the requirements for peel off gel masks by storing at temperatures of 4oC, 25oC, 40oC for 28 days.